A new genus and species of Sternaspidae (Annelida: Polychaeta) from the deep eastern Atlantic - Fiege, Dieter; Barnich, Ruth (European Journal of Taxonomy, 2020)
Based on specimens recently collected in sediments from 2700 m depth off Mauritania (Northwest Africa; type locality) and from 2700–4400 m depth off Angola (Southwest Africa), a new genus and species, Mauretanaspis longichaeta gen. et spec. nov., is described. The new genus and species are characterized by a unique combination of characters: ventro-caudal shield covered by firmly adhering sediment, lateral margins strongly bent and merging into integument; introvert hooks tapering; eight pre-shield segments; absence of peg chaetae; exceptionally long posteriormost lateral chaetae equaling body length; posterior shield chaetae equaling shield length. A comparative table of characters for all currently recognised sternaspid genera and a key to all species with ventro-caudal shield covered by firmly adhering sediment are provided.